Sperm competition games between majors and minors: a meta-regression of fishes with alternative mating tactics - Matto, Lygia Aguiar Del (2018)
Theory predicts that in species with a greater risk of sperm competition, males will invest more in ejaculate traits. In species with alternative mating tactics (AMTs), males of different phenotypes will be under different sperm competition risk. Because minors sneak inside other males\' territories to mate they should always face sperm competition. Major males, on the other hand, defend territories and have more chance of mating exclusively with females. For majors, the risk of sperm competition is theoretically lower. The main prediction from game theory models for species with AMTs is that majors invest less in ejaculate traits than minors. However, when the proportion of minors in the population increases, majors should invest more in ejaculate traits, reaching a similar level of ejaculate expenditure to minors. In this study, we tested these predictions with a meta-regression analysis of 29 fish species with AMTs. As a proxy for the risk of sperm competition, we ranked each species according to a sperm competition rank with five levels, from 1 (low risk of sperm competition) to 5 (high risk of sperm competition). Overall, we found that minors invest more in ejaculate traits than majors. We also categorized the ejaculate expenditure of males, according to the original variables quantified in the studies that were included in our analysis and found that minors invest more energy in the production of gonads than majors. Additionally, minors and majors have a similar investment in sperm number and sperm quality, but majors allocate more sperm to females. Overall, the sperm competition rank did not influence the magnitude of the difference in investment of majors and minors. The differential investment in gonad mass between majors and minors should represent an increase in sperm numbers, but our data showed that majors and minors are not producing different amount of sperm. Therefore, the higher investment in gonad mass can be related to minors mating more frequently than majors. minors are not able to produce sperm in greater quantities than majors, but they probably can replenish sperm faster than majors. Against theoretical predictions, sperm quality does not respond to differences of sperm competition, probably because sperm quality is not under such strong selection as gonad mass. Our findings suggest that, in fishes with alternative mating tactics, both majors and minors are under strong selection from sperm competition, even when the risk of polyandry is low